Analisis Faktor-Faktor yang Berhubungan Dengan Kejadian Ikterus Neonatorum Di Rumah Sakit Budi Kemuliaan - Zulkarnain Edward; Andi Ipaljri; Irene Hafid Amalza (Universitas Batam, 2022)
Background Neonatal jaundice is a yellow discoloration of the baby's skin, conjunctiva, and sclera as a result of increased levels of toxic bilirubin in the blood. Neonatal jaundice is one of the causes of kernicterus and infant mortality. Factors that are thought in cases of neonatal jaundice which are between the baby and the mother. Infant factors consist of gender, low birth weight (LBW), and prematurity in infants. While the maternal factor is the type of delivery. The risk is increased in infants with LBW, prematurity, male sex, and type of cesarean delivery. The purpose of this study was to analyze the factors related to neonatal jaundice at RSBK Batam for the 2017-2020 period. Methods : This study used an observational analytical research design with a cross sectional approach which was carried out in the perinatology room of RSBK Batam in November 2021. The sampling technique was consecutive sampling with a total sample of 124. The results were analyzed by frequency distribution, then tested by chi-square. Results : From the results of this study, it was found that LBW, prematurity, gender, and type of delivery had a relationship with neonatal jaundice. the results of the chi-square statistical test showed p for LBW 0.000, prematurity 0.000, sex 0.003, and type of delivery 0.000 (p<0.05). Conclusion: Based on the results of data management, it can be concluded that there is a significant relationship between LBW, prematurity, gender, and type of delivery with neonatal jaundice at RSBK Batam for the 2017-2020 period.